Governing knowledge: Data, inspection and education policy in Europe - Ozga, J (2012)
The article studies the replacement of bureacratic systems of command and control by networks based on technologies, where co-operation and co-ordination are constantly negotiated and regulated in different ways, and where policy-makers negotiate new power relations with new actors. The comparison between England and Scotland highlights the fact that information and data cannot be transformed immediately into efficient initiatives, and that it requires a constant effort to find a consensus and to preserve it. In the centralised system of England, it is left to technocrats to make this conversion effective. In Scotland, the strategy of self-evaluation is adapted to a discourse of autonomy and progress for all. In both cases, the analysis of the available political tools, as well as the use of information and the role of the school inspectorates enable us to understand the conception of governance for nation-states in a framework of international and European developments. © 2012 Copyright Taylor and Francis Group, LLC.